EFIKASI HERBISIDA PARAKUAT UNTUK PENGENDALIAN GULMA PADA BUDIDAYA KELAPA SAWIT (Elaeis guineensis Jacq) TANAMAN BELUM MENGHASILKAN - Jatmiko Umar Sidik; Dad Resiworo Jekti Sembodo; Rusdi Evizal; Hidayat Pujisiswanto (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
Good plantation management is important to increase the productivity of immature oil palm plants, one of which is chemical weed control. This study aims to (1) determine the dosage of paraquat herbicide which is effective in controlling weeds in the area of immature oil palm plantations, (2) find out the differences in the composition of weed species on immature oil palm plates after application of the paraquat herbicide, (3) find out the phytotoxicity of paraquat herbicides in immature oil palm plants after the application of the paraquat dichloride herbicide. This research was carried out in the farmers' oil palm plantation in Jontor Village, Gayabaru District , Central Lampung Regency and Weed Laboratory of the Faculty of Agriculture, University of Lampung from November 2017 to February 2018. This research used a Randomized Block Design (RBD) with 4 replications and 6 treatments consisting dose of paraquat dichloride herbicide of 375g / ha, 500 g / ha, 625 g / ha, 750 g / ha, and mechanical weeding and without weed control (control). Homogeneity of the various data was tested by the Bartlett test, data additivity was tested by the Tukey test and the difference in the mean was tested with the Least Significant Difference (LSD) test at α 5 level. The result of the study showed that : (1) the herbicide paraquat dichloride dose of 375-750 g / ha effectively control weeds in total, weed leaf width of up to 8 week after application, weed grasses and weeds puzzle to 4 week after application, (2) the herbicide paraquat dichloride dose of 375-750 g / ha is effective in controlling Praxelis clematidea weeds up to 8 week after application, weed Ottochloa nodosa and Asystasia gangetica up to 4 week after application, (3) paraquate dichloride dosage levels 375-750 g / ha resulting in differences in weed composition at 4, 8 and 12 week after application , (4) dosages of 375 - 750 g / ha parakuat dichloride herbicides applied to dishes not poisoning immature oil palm plants.